Imagination and the contemporary novel - Su, John J. (Cambridge University Press, 2011)
"Imagination and the Contemporary Novel examines the global preoccupation with the imagination among literary authors with ties to former colonies of the British Empire since the 1960s. John Su draws on a wide range of authors including Peter Ackroyd, Monica Ali, Julian Barnes, Andre; Brink, J. M. Coetzee, John Fowles, Amitav Ghosh, Nadine Gordimer, Hanif Kureishi, Salman Rushdie and Zadie Smith. This study rehabilitates the category of imagination in order to understand a broad range of contemporary Anglophone literature. The responses of such literature to shifts in global capitalism have often been misunderstood by the dominant categories of literary studies, the postmodern and the postcolonial. As both an insightful critique into the themes that drive a range of today's best novelists and a bold restatement of what the imagination is and what it means for contemporary culture, this book breaks new ground in the study of twenty-first-century literature"--